Additive manufacturing applications of phase‐field‐based topology optimization using adaptive isogeometric analysis. Issue 3 (12th August 2021) - Carraturo, Massimo; Hennig, Paul; Alaimo, Gianluca; Heindel, Leonhard; Auricchio, Ferdinando; Kästner, Markus; Reali, Alessandro
Abstract: In this contribution, we apply adaptive isogeometric analysis to a diffuse interface model for topology optimization. First, the influence of refinement and coarsening parameters on the optimization procedure are evaluated and discussed on a two‐dimensional problem and a possible workflow to convert smooth isogeometric solutions into 3D printed products is described. Second, to assess the required numerical accuracy of the proposed simulation framework, numerical results obtained adopting different stopping criteria are experimentally evaluated for a three‐dimensional benchmark problem.